Rapid strip tests as a decision-making tool about antibiotic treatment in children – A prospective study - Małecki, Mariusz; Mazur, Artur; Sobolewski, Marek; Binkowska-Bury, Monika; Marć, Małgorzata; Januszewicz, Paweł (Pediatria Polska - Polish Journal of Paediatrics, 2017)
x